BICUVOX.1‐matrix composite electrolyte with yttria‐stabilized zirconia as an inert phase: SEM evaluation of the chemical stability under hydrogen atmosphere. Issue 5 (4th May 2015) - Piva, R. H.; Piva, D. H.; Venturini, J.; Floriano, R.; Morelli, M. R.
Summary The purpose of this study is to evaluate the efficacy of yttria‐stabilized zirconia (3Y‐TZP) as an inert phase to prevent the decomposition of Bi2V0.9Cu0.1O5.5−δ (BICUVOX.1) electrolyte under reducing atmosphere. A post‐mortem scanning electron microscopy (SEM) study was performed after chemical stability tests under hydrogen‐rich atmosphere using a Sieverts‐type apparatus. SEM results showed that BICUVOX.1 decomposition starts under a hydrogen pressure of 19.7 atm at 300°C, even in the case of the composite containing 3Y‐TZP. The microstructure of BICUVOX.1 after decomposition was observed to be composed of microspheres ranging from 10 to 100 µm formed primarily of metallic bismuth. In the composite, in addition to microspheres, the microstructure contained bismuth fibers growth from the grain area of the BICUVOX.1 matrix. Despite significant surface morphological modifications, the grain‐boundary‐arranged 3Y‐TZP particles in a BICUVOX.1‐matrix composite did not result in enhanced chemical stability. SCANNING 37:372–379, 2015. © 2015 Wiley Periodicals, Inc.